Making coding fun: why I designed Code-Ninja++ for my students - Tuan Zakaria, Tuan Norhafizah (Universiti Teknologi MARA, Negeri Sembilan, 2025)
Code-Ninja++ was developed to help non-IT students overcome difficulties in learning C++ programming, which often feels complex and intimidating due to unfamiliar syntax and logical structures. Designed as a Progressive Web Application (PWA), the platform allows students to access learning materials easily through a browser without installation. Built using Python (Flask), HTML, CSS, and MySQL, the app serves as a one-stop hub for post-class learning, offering short video tutorials, quizzes, carry mark tracking, past year papers, and gamified features such as leaderboards and badges, while integrating with tools like Padlet, UiTM UFuture, and Quizizz to create a more engaging learning experience.